LA RESPONSABILIDAD SOCIAL UNIVERSITARIA - Carreta, Ana León; Cortes, Luis Carlos Dupeyron; Magaña, Sergio Alfonso Tosca (IJRDO - Journal of Business Management, 2021)
Social responsibility is something that concerns us all because thanks to it allows us to be responsible people capable of dealing with any circumstance in a responsible and honest way, this responsibility has different branches and one of them is the university responsibility that has been growing as a new policy within many universities to get a better response from people and can take on any challenge, As is the case of the DACEA where this new policy was implemented to prepare, this is a very big challenge because it is not easy to adapt to this system which seeks to have people capable of solving any problem in a fast and effective way.